Mikroenkapsulasi ekstrak keratin (protein hewani) bulu ayam broiler (gallus domesticus) sebagai bahan fortifikasi pada susu bubuk: Microencapsulation of keratin extract (animal protein) from broiler chicken feathers (gallus domesticus) as a fortification material for powdered milk - Khuddin, Mukhammad Sholeh; Karimah, Rizka Ajeng; Ummah, Nadifa Zurotul; Maghfiroh, Khoirin (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
In Indonesia, the use of chicken feather waste is currently limited to animal feed, even though chicken feathers contain rich nutritional value, such as keratin. With the application of appropriate technology, chicken feathers have the potential as a functional food ingredient. Currently, in Indonesia, keratin from chicken feathers is usually used in cosmetic products. This research aims to change the status of chicken feathers from waste or animal feed to food additives. Through experimental methods with Ft-ir, SEM, Psa testing and also food safety testing with XRF. keratin is an amino acid. And in the wave number range 2000-3600 cm-1, which is an alcohol peptide bond (O-H). Also found in the wave number range 1480-1575 cm-1 which is the amide II peptide bond (NH bending), and in the wave number range 1229-1301 cm-1 which is the amide III peptide bond (CN Stretching). This indicates that samples A and B both identified the presence of amino acids including cysteine, arginine, lysine, serine and threoni. Thus, the results of this study provide an in-depth understanding of the characteristics of keratin in the context of broiler chicken feathers and the potential and optimization of fortification deficiencies in powdered milk.